ANALISIS HUBUNGAN ANTARA ATRIBUT KONSUMEN DENGAN ATRIBUT PRODUK DALAM KEPUTUSAN PEMBELIAN BUKU DI TOKO BUKU GRAMEDIA SURAKARTA - Chuzaimah, Chuzaimah; Sujadi, Sujadi (Benefit: Jurnal Manajemen dan Bisnis, 2006)
This research aim to analyse relation among consumer attribute (gender, age, earnings and work)with product attribute (promotion, quality of and price) and to know tightest related degree.Formulation this research internal issue do there is relation among consumer attribute covering gender,age, earnings, and work to product attribute covering promotion, quality of, price, and tidiness atBookstore Gramedia Surakarta. Hypothesizing in this research is anticipated there is related amongconsumer attribute covering gender, age, work and earnings to product attribute covering promotion,quality of, tidiness and price at Bookstore Gramedia Surakarta by significant Result of research indicates that there are relation among gender with promotion, quality, price,tidiness. There are relation among age with promotion, quality, price, tidiness, promotion, quality, priceand tidiness. There are relation among work with promotion, quality, price, and tidiness. Calculation of Contiguity among C with Cmaks indicate that related degree sequence amongconsumer characteristic (gender, age, earnings and work) with product characteristic (promotion, qualityof, tidiness and price) having tightest relation is earnings storey with quality, this matter is proved fromvalue contiguity of C with smallest C maks.